Sustainable catalytic epoxidation of biorenewable terpene feedstocks using H2O2 as an oxidant in flow microreactors. Issue 15 (14th July 2021) - Tibbetts, Joshua D.; Cunningham, William B.; Vezzoli, Massimiliano; Plucinski, Pawel; Bull, Steven D.
Abstract : Sustainable solvent-free continuous flow epoxidation of biorenewable terpenes using a recyclable tungsten-based polyoxometalate phase transfer catalyst and benign H2 O2 oxidant. Abstract : Solvent-free continuous flow epoxidation of the alkene bonds of a range of biorenewable terpene substrates have been carried out using a recyclable tungsten-based polyoxometalate phase transfer catalyst and aqueous H2 O2 as a benign oxidant. These sustainable flow epoxidation reactions are carried out in commercial microreactors containing static mixing channels that enable common monoterpenes ( e.g. untreated crude sulfate turpentine, limonene, etc. ) to be safely epoxidized in short reaction times and in good yields. These flow procedures are applicable for the flow epoxidation of trisubstituted and disubstituted alkenes for the safe production of multigram quantities of a wide range of epoxides.